Large scale ontology tailoring and simulation in the Semantic Grid Environment. (2nd April 2007) - Flahive, A.; Apduhan, B.O.; Rahayu, J.W.; Taniar, D.
Ontologies contain semantic information often annotated with metadata. They can get quite complex and very large, causing difficulties in using these ontologies on a daily basis. A large cluster computer is required to tailor these base ontologies into smaller and/or extracted sub-ontologies, but this is expensive and not a viable solution for most users. The Semantic Grid has the ability to process large semantic data repositories as fast as or faster than some of the largest cluster computers at a fraction of the cost. This paper explores the viability of using the Semantic Grid to tailor large ontologies, efficiently and cheaply.